2007
DOI: 10.1007/s00420-007-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of manipulative dexterity in vibration-exposed workers

Abstract: The findings of this longitudinal study suggest an association between deterioration of manipulative dexterity and neurovascular symptoms in the fingers of HTV workers. There was evidence for a significant relation between loss of precise manipulation and exposures to hand-transmitted vibration and ergonomic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Our findings are consistent with the results reported in other studies (6,7,21,22) which found impairment to manual dexterity in groups of workers exposed to hand transmitted vibration. However, our findings could not be directly compared with these results as most of the published studies deal with developed HAVS cases (6,7,31), rarely discussing the biological processes of damage/repair that are relevant for the The decreased grip strength has also been reported (6,8,9).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with the results reported in other studies (6,7,21,22) which found impairment to manual dexterity in groups of workers exposed to hand transmitted vibration. However, our findings could not be directly compared with these results as most of the published studies deal with developed HAVS cases (6,7,31), rarely discussing the biological processes of damage/repair that are relevant for the The decreased grip strength has also been reported (6,8,9).…”
Section: Discussionsupporting
confidence: 94%
“…Manual dexterity loss is a known consequence of vibration exposure (6,7,21,22). It results from (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…As high as 36% of the high exposure group had abnormal Purdue Pegboard test that was used to measure dexterity as compared to only about 14% in the low‐moderate group. This finding is validated by a prospective cohort study among workers exposed to HAV which reported that the Purdue Pegboard score was lower as the HAV exposure level increases during the 1‐year follow‐up . Moreover, the same study also reported that the deterioration of the score over time was associated with worsening of the hand functions in the workers.…”
Section: Discussionsupporting
confidence: 52%
“…This study measured the individual HAV exposure of each worker instead of using company declared values or on representative's samples as used by some other previous studies . Thus, a more accurate and precise exposure level and dose‐response association can be established.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms for musculoskeletal disorders in HAVS usually manifest as ache, pain, stiffness and loss of strength in the fingers, hand, wrist or arm; upper limb tendinitis and osteoarthrosis are common among vibration-exposed workers 3 , 4 , 5 ) . In the later stages, impairments of hand functions like reduced strength and manipulative dexterity may be potentially disabling, and may interfere with work, social and domestic activities 6 ) .…”
Section: Introductionmentioning
confidence: 99%